The Strategies of Tackling the Life Difficulties: Dependence or Independence? - БалабановаЕвгения Сергеевна (Journal of Economic Sociology, 2010)
The author defines the main types of the strategies to tackle the life difficulties taking into account dependence and independence. This task is solved by applying the indicators of social-economic dependence that were worked out by the author in the quantitative empirical study with further tests on the correlation. These dependence indicators are divided into two groups: individual resources (material, social, professional, psychological, health) and purposes (values, orientation on independence and achievements). With the help of multilevel analysis we disclose several groups of people, carrying out different types of strategies.